2001
DOI: 10.1002/ijc.1535.abs
|View full text |Cite
|
Sign up to set email alerts
|

X‐rays modulate extracellular matrix in vivo

Abstract: X-rays have an antiangiogenic effect in the chicken embryo chorioallantoic membrane (CAM) model of in vivo angiogenesis. Our study demonstrates that X-rays induce an early apoptosis of CAM cells, modulate the synthesis and deposition of extracellular matrix (ECM) proteins involved in regulating angiogenesis and affect angiogenesis induced by tumour cells implanted onto the CAM. Apoptosis was evident within 1-2 hr, but not later than 6 hr after irradiation. Fibronectin, laminin, collagen type I, integrin ␣ v ␤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 0 publications
1
27
0
2
Order By: Relevance
“…Modulation of the extracellular matrix after exposure to ionizing radiation is known. 45 The upregulation of metalloproteinase and collagen observed in the present study indicates that ionizing radiation modulates the synthesis and deposition of extracellular matrix proteins involved in regulating angiogenesis. Little information is available concerning the direct effects of radiation on the extracellular microenvironment, specifically the extracellular matrix and its main component, collagen.…”
Section: Discussionmentioning
confidence: 49%
“…Modulation of the extracellular matrix after exposure to ionizing radiation is known. 45 The upregulation of metalloproteinase and collagen observed in the present study indicates that ionizing radiation modulates the synthesis and deposition of extracellular matrix proteins involved in regulating angiogenesis. Little information is available concerning the direct effects of radiation on the extracellular microenvironment, specifically the extracellular matrix and its main component, collagen.…”
Section: Discussionmentioning
confidence: 49%
“…10 In our study, we found that irradiation of C6 glioma cells, although dose dependently decreased their proliferation in vitro, increased the expression and secretion of metalloproteinases 2 and 9 (MMP-2 and MMP-9, respectively), increased the expression of integrin ␣ v and enhanced their angiogenic activity in vivo, when inoculated onto the chicken embryo CAM and in vitro, in cultures of human endothelial cells.…”
mentioning
confidence: 60%
“…[11][12][13] We have previously shown in the in vivo system of the chicken embryo chorioallantoic membrane (CAM) that X-rays enhance angiogenesis induced by C6 glioma cells inoculated onto the tissue immediately after irradiation of the CAM. 10 In our study, we found that irradiation of C6 glioma cells, although dose dependently decreased their proliferation in vitro, increased the expression and secretion of metalloproteinases 2 and 9 (MMP-2 and MMP-9, respectively), increased the expression of integrin ␣ v and enhanced their angiogenic activity in vivo, when inoculated onto the chicken embryo CAM and in vitro, in cultures of human endothelial cells.…”
mentioning
confidence: 60%
See 2 more Smart Citations